A relação rural-urbano a partir das cidades ribeirinhas: o papel do comércio popular (feiras) na cidade de Afuá (PA) - Roni Mayer Lomba; Benedito Baliero Nobre-Júnior (Confins)
The rural-town relationship is discussed through an investigation of popular markets or fairs in the river coastal town of Afuá PA Brazil. The several supply networks in the town and its intra-regional movements have wide connections underscored by the river that boosts the commerce of in natura or industrialized regional products and goods. Commerce dynamism is focused in current research which is performed through the investigatory method and analyzes theoretical contributions, interviews, photos and reflections, which are instruments that underpin its materialization. Current investigation re-considers the concepts and definitions of the countryside-town and rural-urban relationships within the context of the river coastal towns of the Amazon. It also investigates the specificities of the rural-urban relationship in Afuá from the point of view of commercial dynamics. In fact, its importance within the several movement networks, namely cultural, economical and symbolic, that supply the town, is demonstrated. Results show an intrinsic countryside-town and rural-urban relationship of the Amazon coastal towns. Even within the modernization context the economical and social relationships have not disrupted the way of life or the territoriality historically built and still extant in the region.